Terminología cromática aleuta - Alonso de la Fuente, José Andrés (Revista Española de Antropología Americana, 2008)
The scope of this paper is to analyze the Aleut chromatic lexicon in order to check whether it follows the existing “universals” claimed by Berlin and Kay few decades ago. As it will be showed, Aleut belongs to those languages that do not follow them. In fact, by means of etymology shall be demonstrated that the formation of such chromatic vocabulary in Aleut is recent and secondary.